Photoresist Design for Elastomeric Light Tunable Photonic Devices - Nocentini, Sara (Materials (Basel), 2016)
An increasing interest in tunable photonic structures is growing within the photonic community. The usage of Liquid Crystalline Elastomer (LCE) structures in the micro-scale has been motivated by the potential to remotely control their properties. In order to design elastic photonic structures with a three-dimensional lithographic technique, an analysis of the different mixtures used in the micro-printing process is required. Previously reported LCE microstructures suffer damage and strong swelling as a limiting factor of resolution. In this article, we reported a detailed study on the writing process with four liquid crystalline photoresists, in which the percentage of crosslinker is gradually increased. The experiments reveal that exploiting the crosslinking degree is a possible means in which to obtain suspended lines with good resolution, quite good rigidity, and good elasticity, thereby preserving the possibility of deformation by light irradiation.